Odpowiedzi

Najlepsza Odpowiedź!
2009-10-14T21:48:42+02:00
A) 5,1×(0,6- ⅖ × 0,5) = 5,1*(0,6-0,4*0,5) = 5,1*(0,6-0,2) = 5,1*0,4 = 2,04

b) 7,3 × ½ -0,8 ÷0,03 = 7,3*0,5-26⅔ = 3,65-26,67 = -23,02

c) ⅗ - (1,6- ⁵/₁₆ -0,3)×11 = 0,6 - (1,3-⁵/₁₆)*11 = 0,6 - (208/160-50/160)*11 = 0,6 - (158/160)*11 = 6/10 - 1738/160 =
6/10 - 869/80 = 48/80 - 869/80 = -821/80 = -10 21/80
2009-10-14T22:35:39+02:00
5,1x(0,6-2/5x0,5)=5,1x(0,6-0,4x0,5)=5,1x(0,6-0,2)=5,1x0,4=2,04

7,3x1/2-0,8:0,03=73/10x1/2-8/10:3/100=73/20-8/10x100/3=3i13/20-
-80/3=26i2/3=3i39/60-26i40/60=-23i1/60

3/5-(1,6-5/16-0,3)x11=3/5-(1i6/10-5/16-3/10)x11=3/5-(1i96/160-50/160-48/160)x11=3/5-1i2/160x11=3/5-1i1/80x11=3/5-11i11/80=48/80-10i91/80=-10i43/80